A genetic locus for paranoia. (17th January 2018) - Crespi, Bernard; Read, Silven; Salminen, Iiro; Hurd, Peter
Abstract : The psychological effects of brain-expressed imprinted genes in humans are virtually unknown. Prader–Willi syndrome (PWS) is a neurogenetic condition mediated by genomic imprinting, which involves high rates of psychosis characterized by hallucinations and paranoia, as well as autism. Altered expression of two brain-expressed imprinted genes, MAGEL2 and NDN, mediates a suite of PWS-related phenotypes, including behaviour, in mice. We phenotyped a large population of typical individuals for schizophrenia-spectrum and autism-spectrum traits, and genotyped them for the single-nucleotide polymorphism rs850807, which is putatively functional and linked with MAGEL2 and NDN . Genetic variation in rs850807 was strongly and exclusively associated with the ideas of reference subscale of the schizophrenia spectrum, which is best typified as paranoia. These findings provide a single-locus genetic model for analysing the neurological and psychological bases of paranoid thinking, and implicate imprinted genes, and genomic conflicts, in human mentalistic thought.